(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
White Collar Crimes are to be considered as a worldwide wonder to which India is no exemption. White Collar Crimes rose in India with the approach of the British colonization amid the time of Industrial Capitalism. Preceding that, occasions of men working with the District treasury stealing with the cash held under safe guardianship or influencing rehearsed among the authorities were found. Along these lines, the White Collar Crimes were kept as far as possible. In this manner, the general population enjoying the White Collar Crimes at that point can said to be simple ’grass eaters’ when contrasted with the general population in the advanced occasions having reached the phase of ’meat-eaters’.Researcher has concentrated to investigate the Constitutional Provisions and different Laws identified with control the White Collar Crimes these crimes are hurtful for the economy of the nation. The object of the investigation is to test present laws and to discover the lacunae, to contrast our laws and created nations and to expel the insufficiency in our laws. The analyst has featured the Role of different Committees and Agencies to get the Corruption and investigated the association of Cyber Criminals in cases of Corruption and in a roundabout way or specifically such crimes are advancing the degenerate exercises influencing economy of India. Thus, the opportunity has already come and gone to make individuals mindful of the results all things considered and usual way of doing things of perpetrating White Collar Crimes.